2015
DOI: 10.1038/srep08921
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Magnetic Semiconductor Behavior in Zigzag Phosphorene Nanoribbons Driven by Half-Filled One Dimensional Band

Abstract: Phosphorene, as a novel two-dimensional material, has attracted a great interest due to its novel electronic structure. The pursuit of controlled magnetism in Phosphorene in particular has been persisting goal in this area. In this paper, an antiferromagnetic insulating state has been found in the zigzag phosphorene nanoribbons (ZPNRs) from the comprehensive density functional theory calculations. Comparing with other one-dimensional systems, the magnetism in ZPNRs display several surprising characteristics: (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(48 citation statements)
references
References 43 publications
5
43
0
Order By: Relevance
“…Since pristine phosphorene is a nonmagnetic semiconductor, it cannot be directly used in the field of spintronics, however, different strategies such as edge cutting structures [18][19][20][21][22], doping with non-magnetic adatoms [23][24][25], or atomic defects (vacancies and adatom adsorption) [17,26,27] have been suggested to induce magnetic behaviors in phosphorene. For instance, it is found that due to the magnetic instability induced by the halffilled edge bands crossing the Fermi level, phosphorene nanoribbons (PNRs) with bare zigzag edges are antiferromagnetic semiconductors [19]. This magnetization also causes to the opening of a significant direct band gap (about 0.7 eV), which transforms the metallic PNRs into semiconductors ones.…”
Section: Introductionmentioning
confidence: 99%
“…Since pristine phosphorene is a nonmagnetic semiconductor, it cannot be directly used in the field of spintronics, however, different strategies such as edge cutting structures [18][19][20][21][22], doping with non-magnetic adatoms [23][24][25], or atomic defects (vacancies and adatom adsorption) [17,26,27] have been suggested to induce magnetic behaviors in phosphorene. For instance, it is found that due to the magnetic instability induced by the halffilled edge bands crossing the Fermi level, phosphorene nanoribbons (PNRs) with bare zigzag edges are antiferromagnetic semiconductors [19]. This magnetization also causes to the opening of a significant direct band gap (about 0.7 eV), which transforms the metallic PNRs into semiconductors ones.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the similar behavior was observed in black phosphorene nanoribbon. 29 Along with the change in the magnetic state, the band structure was also modified due to the external strain. We found that the band gap disappeared at the compressive strain (>4%) and the ZBPNR became metallic.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies show that the edges passivation with various species present different properties, 21 and also an external strain on the nanoribbons can change the edges magnetism drastically. 29 Therefore, we will explore the effect of edge passivation and strain effect on the edge magnetism as well.…”
mentioning
confidence: 99%
“…A number of methods can be applied to control magnetism of ZGNRs, among which are doping and edge-modification [2,3,8]. Edge magnetism has also been proposed in other 2D materials such as MoS 2 [9], black phosphorus (BP) [10] and ZnO [11]. One of the most interesting aspects of edge magnetism is halfmetallicity.…”
Section: Introductionmentioning
confidence: 99%